Ferramentas interativas em ambientes virtuais de aprendizagem e sua usabilidade pedagógica nos cursos de educação a distância da UFAL e IFAL - Silva, Flávio Pereira da (2010)
The work exposed here is to provide a Model Gauging Usability in Virtual Learning Environments - VLE in the context of Distance Learning - DL, courses applied to this type of teaching, under the Public Institutions of Higher Education of Alagoas, Brazil: Universidade Federal and Instituto Federal. Variant of the proposed concept of Usability by Jakob Nielsen. It is a setting little studied and widespread; Based on studies of Petri Nokelainen, Pedagogical Usability is tied to the context of production material in DL for the VLE and methodological choices in the teacher-author realizes. The dimensions suggested by the model are: Learner Control, Learner Activity, Cooperative / Collaborative Learning, Goal Orientation, Applicability, Added Value, Motivation, Valuation of Previous Knowledge, Flexibility and Feedback. Based on these dimensions was generated a questionnaire later applied to the students belonging to the both schools. Two hundred and sixty-one students were analyzed. The data processing was conducted by SPSS platform, you can reach the results of: Moodle virtual environment was better measured in terms of usability; Women were more motivated and independent; IFAL stood out as a educational institution applying its methodology teaching material preparation and teaching within the AVA's.